Endothelin-1 signaling maintains glial progenitor proliferation in the postnatal subventricular zone - Katrina L. Adams; Giulia Riparini; Payal Banerjee; Marjolein Breur; Marianna Bugiani; Vittorio Gallo (Nature Communications, 2020)
Endothelin-1 (ET-1) is a vasoconstrictor molecule that is also present in the developing and injured CNS. Here the authors show that ET-1 is present in the postnatal subventricular zone and acts to regulate maintenance and proliferation of radial glial cells and oligodendrocyte progenitor cells.